2021
DOI: 10.1097/dbp.0000000000001046
|View full text |Cite
|
Sign up to set email alerts
|

Society for Developmental & Behavioral Pediatrics Position Statement on Telehealth

Abstract: Telehealth has long held promise as a way to increase access to subspecialty care for children and families, including in developmental and behavioral pediatrics (DBP). The coronavirus disease 2019 (COVID-19) pandemic necessitated rapid uptake of telehealth to continue care delivery that was facilitated by "temporary" policy changes related to the pandemic. As a result, the field of DBP has recognized telehealth as a potential model of care for performing home-based diagnostic assessments, providing medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…These results reinforce the literature that emphasizes the need to increase access to broadband and suitable devices for children with NDD. 15 Further research is needed on the best way to assess the technology needs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results reinforce the literature that emphasizes the need to increase access to broadband and suitable devices for children with NDD. 15 Further research is needed on the best way to assess the technology needs.…”
Section: Discussionmentioning
confidence: 99%
“…
Use images to assist with communication barriers Utilize inclusive intake processes to ask about technology access 21 Consider closed captioning options for persons with hearing impairment Identify community resources that offer free internet access Permit patients to access telehealth from any safe, physical location to decrease barriers to access 15 Provide guidance on telehealth visits at an in-person visit
…”
Section: Clinics Care Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 There has been a proliferation of research on telehealth as a possible strategy to mitigate in-person service losses for children with autism. [9][10][11] Before the pandemic, feasibility and potential efficacy of telehealth interventions have been demonstrated for individuals with ASD in several systematic reviews. 12,13 A small telehealth occupation-based coaching intervention study conducted before COVID-19 found significant gains in parent efficacy, in various domains of child participation, and in parent-identified goals postintervention.…”
mentioning
confidence: 99%